Precarious work and its impact on health: a study of female textile workers in Lahore and Faisalabad - Khan, Muhammad; Amir-ud-Din, Rafi; Atif, Rao Muhammad (Frontiers in Public Health, 2025)
IntroductionThis study aimed to examine work conditions, wage disparities, and health outcomes among female textile workers in Lahore and Faisalabad districts, employing a cross-sectional design to survey 541 participants.MethodsUtilizing the Respiratory Health Questionnaire, validated with a Cronbach alpha of 0.7762, alongside OLS and Logit regression models, the research investigated the interplay between employment conditions and health risks.ResultsThe analysis revealed significant wage discrepancies, with permanent employees earning PKR 1,896 more on average than their temporary counterparts (p < 0.01), and identified a strong correlation between employment type, excessive work hours, and health issues. Permanent contracts were associated with a 2.4-fold increase in the likelihood of excessive work hours (p < 0.01), while higher wages and dustier work environments were positively correlated with longer working hours. Conversely, social security benefits were linked to reduced excessive work hours (OR = 0.060956, p < 0.01). Furthermore, precarious work conditions, notably overtime and temporary contracts, significantly elevated the risk of respiratory problems and other health issues, with overtime work markedly increasing the likelihood of adverse health outcomes, including blood phlegm (OR = 11.285, p < 0.01) and fatigue (OR = 7.579, p < 0.01).DiscussionThe findings underscore the critical need for policy interventions to improve work conditions, enforce minimum wage and work hour standards, and ensure the provision of social security benefits to mitigate health risks among this vulnerable worker group.